Analysis of Stress Distribution and Displacement Based on the Miniscrew Positions of the Palatal Slope Bone-borne Expander: A Finite Element Study - Leeisaramas, Chakree; Chantarapanich, Nattapon; Inglam, Samroeng; Insee, Kanlaya (European Journal of Dentistry, 2024)
Objectives This study aimed to investigate the stress distribution pattern of the palatal slope bone-borne expander on the maxillary area according to a different anteroposterior position of anchored miniscrews using finite element analysis.Materials and Methods Nasomaxillary stereolithography files with three different anteroposterior anchored miniscrew positions of the palatal slope bone-borne expander were determined as model A, B, and C. Each model consists of four supported miniscrews. Model A: two anterior miniscrews were located between the maxillary canine and the first premolar, and two posteriors between the second premolar and the first molar. Model B: two anteriors were between the lateral incisor and the canine, and two posteriors were the same as in model A. Model C: two anteriors were the same as in model A, and two posteriors were distal to the first molar. One turn of expander screws was applied. Maximum principal stress, equivalent elastic strain, equivalent von Mises stress, and transverse displacement were evaluated.Results The maximum principal stress was mostly found at the bone-miniscrew interface. Model A exhibited an intersecting area of stress between the supported miniscrews. The highest value of principal stress was in model B, while model C showed a uniform distribution pattern. The elastic strain pattern was similar to the principal stress in all models. The highest value of equivalent von Mises stress was located on the expander screw. The largest amount of transverse displacement of teeth was in model A, while model C exhibited a more consistent transverse displacement than other models. Vertical displacement of posterior teeth was also noticed.Conclusion Based on the result, it revealed that the various anteroposterior miniscrew placements of the palatal slope bone-borne expander had various patterns of stress distribution and resulted in various outcomes. It may be inferred that model A's miniscrew location was advantageous for obtaining expansion quantities, but model C's miniscrew position was advantageous for maintaining consistent biomechanics.
Keywords: palatal slope bone-borne expander; miniscrew positions; stress distribution; nasomaxillary area; finite element